2020
DOI: 10.1007/978-3-030-47679-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach Applied to the Prevalence Analysis of ADHD Symptoms in Young Adults of Barranquilla, Colombia

Abstract: Disorder Attention Deficit/Hyperactivity Disorder, or ADHD, is recognized as one of the pathologies of high prevalence in children and adolescents from the global environment population; this disorder generates visible symptoms usually diminish with the passage of time in adulthood, however they remain concealed by demonstrations damnifican personal stability and human development apt. This article shows the results of the research aimed at determining the prevalence of symptoms of attention deficit hyperactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As for the Beta band, which is associated with intense brain activity, active thinking, and focus [41], the connections in the frontal and cognitive electrodes provided insight into the attention the HC subject had during the target stimulus, which we did not observe in the MCI subject (Figure 7c,d). Figure 7 focuses on the brain connectivity of MCI and HC subjects.…”
Section: Interpretability From Functional Connectivity-wpli According...mentioning
confidence: 76%
See 3 more Smart Citations
“…As for the Beta band, which is associated with intense brain activity, active thinking, and focus [41], the connections in the frontal and cognitive electrodes provided insight into the attention the HC subject had during the target stimulus, which we did not observe in the MCI subject (Figure 7c,d). Figure 7 focuses on the brain connectivity of MCI and HC subjects.…”
Section: Interpretability From Functional Connectivity-wpli According...mentioning
confidence: 76%
“…In the context of cognitive impairment, we used graph theory to study how neuronal network changes affect information flow, leading to symptoms such as memory loss or difficulty with decision-making [45]. Previous studies have shown that subjects with AD and MCI have decreased BC in specific brain regions [41], suggesting that these channels (respective regions) may play a role in the disease and that changes in their connectivity could contribute to cognitive impairment; however, more research is required to understand the relationship between graph theory, centrality measures, and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations